A Foucauldian Theory of American Islamophobia - Sriram, Shyam K. (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
With the emergence of ISIS andAmerican public furor over allowing Syrian refugees safe haven, Muslim Americans find themselves once again in the cross-hairs of a nation obsessed with searching for answers and someone to blame. I argue that the premise behind American anti-Muslim sentiment is rooted in two of Michel Foucault’s concepts -“biopower” and “pastoral power.” This article is divided in two halves. In the first, I argue that American nationalism is articulated in a unique way, particularly through “pastoral power.” In conjunction with an “imagined” American nationhood (Anderson 1983), it has created a state that is often viewed as secular, but is quite Christian ideologically and structurally. Drawing on Göle (1996), I surmise that the Western “culture of confession,” an extension of pastoral power, is incompatible with Islam – or at least is viewed as such. In the second half, I present my main argument towards a new understanding of Foucault’s (1990) biopower in the context of the sovereign and its ability to designate who is “sacred,” a la Agamben (1998). I suggest that a new evaluation of Agamben (1998) should be undertaken to account for the renewed racialization of and discrimination towards American Muslims.